1996
DOI: 10.1037/0022-3514.70.4.868
|View full text |Cite
|
Sign up to set email alerts
|

Self-handicapping and intrinsic motivation: Buffering intrinsic motivation from the threat of failure.

Abstract: High and low self-handicappers (as measured by E. E. Jones & F. Rhodewalt's [1982] Self-Handicapping Scale) were asked to play a game of pinball (in a competitive or noncompetitive setting) after they had practiced as much as they wanted on a related task (thus, not practicing could have served as a self-handicap). High self-handicappers who did not practice much became more involved in the game and subsequently reported enjoying the game more than high self-handicappers who practiced a lot. Furthermore, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 27 publications
1
37
1
3
Order By: Relevance
“…Our results are consistent with the findings of previous research in which high self-handicappers students engaged in self-handicapping in a situations with low evaluative components (Rhodewalt & Fairfield, 1991, studies 1 and 2) or in a noncompetitive task (Deppe & Harackiewicz, 1996). Our findings, however, differ from these studies on three points.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations
“…Our results are consistent with the findings of previous research in which high self-handicappers students engaged in self-handicapping in a situations with low evaluative components (Rhodewalt & Fairfield, 1991, studies 1 and 2) or in a noncompetitive task (Deppe & Harackiewicz, 1996). Our findings, however, differ from these studies on three points.…”
Section: Discussioncontrasting
confidence: 42%
“…Rather, they suggest that high self-handicappers may engage in behavioral selfhandicapping even in low ego-threatening situations. Further, in an other study that was designed to investigate the consequences of self-handicapping on performance, Deppe and Harackiewicz (1996) observed that high self-handicappers engaged in more behavioral self-handicapping compared with low self-handicappers before participating in a pinball game both in a competitive condition (that included a high evaluative component) and in a noncompetitive condition (that lacked an evaluative component).…”
Section: Claimed Self-handicapping In Low Ego-threatening Situationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies show negative effects (Rhodewalt, Morf, Hazlett, & Fairfield, 1991) and some show no effects at all (Greenberg, Paisley, & Pyszczynski, 1984). Some studies even suggest that self-handicapping may act as a buffer against anxiety and ability attributions thus leading to performance benefits (Deppe & Harackiewicz, 1996). Most studies focusing on habitual self-handicapping (i.e., selfreported preference for self-handicapping behavior) have found evidence linking selfhandicapping with maladaptive outcomes.…”
Section: The Present Studymentioning
confidence: 99%